Evaluation of Alternative Diagnostic Techniques for Diagnosis of Cerebral Malaria in a Tertiary Referral Hospital in Bangladesh (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):180-5.The abstract of this article is available on the PubMed website